Analysis of the Business Model for Independent Fish Feed Manufacturing Using the Business Model Canvas Approach - Hamsinah Hamsinah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
One of the main obstacles in fish farming is the problem of feed. Feed absorbs up to 70% of the production cost of fish farming, where most of the feed needs are met from fish feed manufacturers. The price of factory feed currently circulating is still considered high by fish cultivators, especially freshwater fish cultivators. Thin profit margins do not provide adequate incentives for freshwater fish farmers to develop their businesses so as to increase their level of welfare. Therefore, there needs to be an effort from the government to overcome feed problems, especially in terms of providing quality fish feed at affordable prices so that feed is no longer an obstacle in the development of aquaculture, especially freshwater aquaculture. The purpose of this study was to analyze the business model of making fish feed using the canvas method. The method used in this study uses a qualitative approach. Data obtained through research, be it interviews, observations, etc., are reliable, contain honesty, are objective and can be accounted for. This qualitative approach is used as a research procedure that produces descriptions in the form of written words. or verbal from people and observable behavior. The results of this research are very good and have potential for the community.